Analisis Maqashid Syariah Tentang Efektivitas Pelaksanaan Program Bantuan Sosial Usaha Mikro Kecil Dan Menengah (Studi Kasus Desa Mekarmukti Kecamatan Cilawu Kabupaten Garut) - Syaripudin, Enceng Iip; Patonah, Fitri (STAI Al Musaddadiyah Garut, 2022)
In the Islamic view, a state plays a central and at the same time fully responsible role in all the affairs of its people. The state has the obligation to ensure the realization of an atmosphere of ta'abud (ease of worship), welfare such as providing guarantees for basic needs. Social Assistance for Micro, Small and Medium Enterprises (MSMEs) is an effort to help business capital affected by the economic crisis. Social Assistance for Micro, Small and Medium Enterprises (MSMEs) is cash assistance provided to business actors, but the distribution of assistance is indicated to be not right on target. The formulation of the problem in this study: 1) How effective is the implementation of the distribution of social assistance for Micro, Small and Medium Enterprises to people in need. 2) How is the analysis of sharia Maqashid on the effectiveness of the implementation of social assistance distribution for Micro, Small and Medium Enterprises in Mekarmukti Village, Cilawu District, Garut Regency. The objectives of the study are: to determine the effectiveness of the implementation of social assistance distribution for Micro, Small and Medium Enterprises (MSMEs) to people in need in Mekarmukti Village, Cilawu District, Garut Regency and To analyze sharia Maqashid on the effectiveness of the implementation of MSME social assistance distribution in Mekarmukti Village, Cilawu District, Garut Regency The research methods used are field research (Field research) and literature research (Library) Research). This research is qualitative research, which is normative descriptive research. From the results of the study, it was concluded that the success of the Government Assistance Program for Micro Entrepreneurs in Mekarmukti Village, Cilawu District has not been successful as a whole, in terms of distribution of aid to recipients, some are not right on target to recipients who do not have a business, some should be entitled but their names do not come out as potential beneficiaries. Keywords: Maqashid Sharia, effectiveness, micro.